Corporate Governance and Financial Performance in Nepal - Lamichhane, Pitambar (NCC Journal, 2018)
This paper analyzes the factors that affect corporate governance and influence on financial performance of Nepalese firms for theperiod of fiscal year 2009/10 to 2015/16 using descriptive and causal comparative research design. The profit margin and return on assets are dependent variables usedto measure financial performance and corporate governance and firm related variables such as corporate governance index, age of firms, size of assets, debt ratio, market to book ratio and ownership concentration are considered as explanatory variables. The result of this paper reveals thatprofit margin and return on assets of firms are positively related with age, market to book ratio and overall corporate governance index which implies that higher age, market to book ratio and corporate governance increase financial performance of Nepalese firms. Further, the regression result of the study shows that size of assets and debt ratio have negative effect and ownership concentration has no relationship with firms’ financial performance. Finally, result of this paper concludes that corporate governance, market to book value ratio, age, size of assets and debt ratio have strong explaining power of financial performance of Nepalese firms. NCC Journal Vol. 3, No. 1, 2018, Page: 108-120